Free internal mammary artery for coronary bypass. Issue 2 (April 1976) - Vidne, B A; Lee, A B; Lajos, T Z; Schimert, G
Abstract : An improved technique of free internal mammary artery (IMA) to ascending aorta anastomosis for coronary bypass is described. A small patch vein with a suitable side branch or branches is interposed, connecting the proximal end of a detached IMA to the ascending aorta. A single or double free IMA alone or in combination with an additional saphenous vein graft was performed in 77 patients. A total of 125 free IMA grafts were done. The hospital mortality was 2-7% and late mortality 1-4%. Seventy-one of the 74 surviving patients had no angina and returned to a normal life. Postoperative coronary arteriography in 65 patients showed a patency rate of 96%. On year's experience with this technique is very encouraging. However, prolonged follow-up is necessary to determine if free IMA, as used by us, will increase the long-term patency rate.